Quantity‐insensitive iambs in Osage1 - Altshuler, D (University of Chicago Press, 2009)
This paper presents evidence for the quantity‐insensitive iamb. Although many extant prosodic theories predict that qi iambs exist (e.g., Prince and Smolensky 2004, McCarthy and Prince 1993, and Halle and Vergnaud 1987), previously reported cases have not been verified by phonetic analysis. Some authors have even questioned the existence of qi iambs (e.g., Hayes 1995). The consequence of the existence of qi iambs is that foot headedness and quantity sensitivity are independent: whether a foot is trochaic or iambic is unrelated to whether it is also quantity‐sensitive.